Establishment of a National ecological network to conserve biodiversity. Pros and cons of ecological corridors Establishment of a National ecological network to conserve biodiversity. Pros and cons of ecological corridors - Laurent Bergès, Philip Roche and Catherine Avon (Sciences, Eaux & Territoires, 2011)
Ecological corridors are a fundamental element in the National ecological network approved by the Grenelle environmental agreement in order to reduce ecosystem damage caused by fragmentation of the natural habitat zones of species. How can their effectiveness be evaluated? This article sums up current knowledge on their pros and cons. Fragmentation of natural habitats is considered one of the main causes of biodiversity loss. One of the proposed solutions to limit the effects of fragmentation is to restore ecological connectivity by creating ecological corridors between zones containing natural habitats. The concept remains controversial among scientists, but now serves as the basis for one of the operational projects of the Grenelle environmental agreements in the form of the National ecological network. After examining the ecological concepts justifying the political goal and presenting the various ecological roles of corridors, we briefly discuss their overall advantages and disadvantages. Then, we look closely at the methodological difficulties in detecting a corridor effect. Finally, we recommend a close partnership between research and policy to design biodiversity monitoring and evaluation systems in the different land-management plans.